Active and inactive forms of biotin synthase occur in Heterodera glycines - Kwon, Khee Man; Bekal, Sadia; Domier, Leslie L.; Lambert, Kris N. (Journal of nematology, 2019)
, the soybean cyst nematode (SCN), is a plant-parasitic nematode capable of manipulating host plant biochemistry and development. Many studies have suggested that the nematode has acquired genes from bacteria via horizontal gene transfer events (HGTs) that have the potential to enhance nematode parasitism. A recent allelic imbalance analysis identified two candidate virulence genes, which also appear to have entered the SCN genome through HGTs. One of the candidate genes, biotin synthase ( ), contained sequence polymorphisms between avirulent and virulent inbred SCN strains. To test the function of these alleles, a complementation experiment using biotin synthase-deficient was conducted. Here, we report that avirulent nematodes produce an active biotin synthase while virulent ones contain an inactive form of the enzyme. Moreover, sequencing analysis of genes from SCN field populations indicates the presence of diverse mixture of alleles with the virulent form being the most prevalent. We hypothesize that the mutations in the inactive allele within the virulent SCN could result in a change in protein function that in some unknown way bolster its parasitic lifestyle.